The effect of a communicational program on psychological distress in the elderly suffering from cancer - Fateme Hejazi; Masoud Bahrami; Mahrokh Keshvari; Mousa Alavi (Wolters Kluwer Medknow Publications, 2017)
Background: Psychological distress is one of the most common psychological symptoms in elderly cancer patients. However, many of these patients do not receive any treatment for distress management. Therefore, we aimed to assess the effect of a communication program on the psychological distress of elderly cancer patients. Materials and Methods: This two-group clinical trial with a before and after design was conducted in Al-Zahra and Seyed-Al-Shohada hospitals affiliated to the Isfahan University of Medical Sciences in 2015. A total of 64 elderly patients were randomly assigned to two groups: experimental and control groups. A 3-week intervention (communicational program) consisting of distributing educational booklets, practices, and phone follow-ups was performed for the intervention group. All sessions were held during the 3-week period with sessions held twice per week both in the form of personal attendance and phone tracking, and the patients were encouraged to do the tasks assigned to them. The control group received routine care, and at the end of the study, the content of the sessions was explained to them. The demographic and clinical data of the participants were recorded, and all participants completed Kessler's Psychological Distress inventory at baseline and at the end of the 3-week intervention. Results: We found a significant difference in the psychological distress scores between the two groups before and after the intervention (P < 0.001, independent t-test). Moreover, the mean psychological distress scores decreased significantly in the experimental group after the intervention (P < 0.001, paired t-test). Conclusions: Our communicational program had a positive effect on psychological distress in elderly patients with cancer. Therefore, this program could be used as an easy, cheap, and practical approach for reducing psychological distress in these patients.